Hidrogel como condicionador de substrato para produção de mudas de Eucalyptus dunnii Maiden - Navroski, Marcio Carlos (2013)
The use of polymers hidroretentores mixed to the substrate, has the function of water retention and release in a gradual way to the plant, and may increase the efficiency of irrigation, reducing the consumption of water and fertilizers. The objective of this research was to evaluate the feasibility of using the hydrogel substrate added to the sowing of seedlings, verifying the chemical and physical properties on the substrate and the reflection on the growth of seedlings. The work was divided into six chapters, in Chapter I tested different dosages of polymer substrates and vegetable. The chemical and physical analysis of substrates and growth of seedlings demonstrate the improvement of the properties of the substrates, especially those related to water retention, and reflection on the growth of seedlings in the nursery. The use of 4 g L-1 of the hydrogel showed overall the best seedling development. In Chapter II we evaluated the relationship of the hydrogel with doses of controlled-release fertilizer. The use of the hydrogel showed improved physical and chemical characteristics of substrates, especially attributes involving storage and delivery of water to plant. The use of polymer hidroretentor in seedlings of Eucalyptus dunnii can reduce the use of fertilizer in 25 - 50% on average, with no loss in quality seedlings. The Chapter III was on the evaluation of the strengths-based polymer polyacrylamide seedling growth and the characteristics of the substrate, in addition to nutritional analysis after cultivation of seedlings in the nursery. The dosage around 4.5 g L-1 brings the best answer regarding morphological. The use of doses below 3 g L-1 or above 4.5 g L-1 could negatively influence the majority of the observed features. All the nutrients had a higher nutritional content in shoots in the presence of the hydrogel, as compared to micronutrients, there was a decrease in the content of all elements with increasing polymer dosage. Check the effect of the hydrogel in different irrigation was the goal in Chapter IV. In the absence of the hydrogel, the further development of seedlings was obtained with irrigation between 16 to 20 mm day -1. In the presence of 3 g L-1 hydrogel further development of seedlings was obtained with the irrigation of 12 mm day -1. In Chapter V we tested the effect of hydrogel in planting seedlings in pots, relating to irrigation frequencies. The polymer hidroretentor possible delay of all symptoms of water deficit assessed with higher influence when irrigation is performed less frequently. The economic evaluation of the costs with the use of hydrogel was discussed in Chapter VI. The use of lower doses, together with savings from the reduction of fertilization and especially with the water, the use of the hydrogel may represent reduction of production costs. In general, the results obtained with regard to the use of polymers hidroretentor confirm the information which hydrogel addition of the substrate optimizes the availability of water by accelerating the development of plants therefore better performance in absorbing water and nutrients.